한국의 이주민 대상 언어교육: 현황과 제언 - 조정순(Jeongsoon Joh) (영어학, 2024)
The purpose of the present study is to examine the status quo of language education for the immigrants in Korea in an effort to suggest the more workable ways to help them successfully adapt to the host country and appropriately function as a qualified member in the society. The practices in the U.S.A., which has a long history in this area, were surveyed first focusing on the empirical approaches to, and the major issues involved in, teaching the language of the host country to the immigrants. The current state of language education for immigrants in Korea was then examined largely based on the official documents from the Korean government offices. Results indicate that more systematic and rigorous management would be necessary for the language education policy targeted at immigrants to be implemented as originally intended, while the policy itself seems generally well grounded on theoretical basis and coherently structured at least at the administrative level. Discussion on the current practices in the relevant area and suggestions for further research on this issue are stated, along with limitations of the present study. KCI Citation Count: 0